أحكام عقد البيع الالكتروني: دراسة تحليلية مقارنة - د. عبد الرحمن أحمد المساعد - أستاذ مساعد (White Nile Journal for Studies and Research, 2018)
This study comes under the address of compromising in the deals of electronic trades, considering that compromising is the base to establish deals, it goes around the idea of willing and how to express it by ways of approval and acceptance using modern electronic means that are different in it's nature it gives speed to accomplishment and properties from other traditional means and execution so to make a big ratio of overall accomplished deals. The importance in expressing wills becomes clear in compromising being the base and essence of deals process, as it goes hand to hand with the Islamic legislation spirit, electronic compromising found strong solid floor to be accepted and used. As of it the majority of electronic deals became confined to the special provisions of compromising. The compromising research also takes on existence of electronic will and expressing it by the ways of offering and approval. The range of validity of this will is to create commitment in the deals of electronic trades, and mark the deal board concepts, images, nature and circumstances facing two wills in it. The research reached a lot of results which are: Significant increasing of electronic trades and not limiting on accomplished deals from the internet. Two dealers must express their wills on electronic trades deals in any ways possible, as long as this mean shows in an affirmative way the true goals which has been agreed. It also reached some recommendations, most important of it is: The researcher is recommended to take time measurements to distinguish contracting between two presents and two absents, it's the most suitable way because of it's flexibility and ability to keep up with the development on used means to make deals. Necessity to expand by using the theory of apparent situation is to fix the problem of determining the identity of parties of contractual relationships and the extent of their eligibility to make deals by the internet.